Le désengagement de l'Etat de la gestion des affaires économiques : une solution à la crise des entreprises publiques du Sénégal - Badji, Marie Suzanne (Université Cheikh Anta Diop, 2002)
Keywords: Entreprise publique; Etat (désengagement); Gestion; Sénégal

Community competence to control mergers : the jurisdictional divide - Burnley, Richard (European University Institute, 2002)
Keywords: Antitrust law; European Union countries; Unfair Competition

Globalization and the limits of National merger control laws: gaps in global governance and the need for an international merger control regime - Wilson, Joseph (McGill University, 2002)
From an economic perspective, globalization is dismantling national barriers to entry and is transforming domestic markets into a global market. To meet the challenges posed by the integration of markets, corporations are joining forces with their former competitors to expand their presence in the global market. Rapid growth in transnational mergers to create global corporations is one of the key features of globalization. As multinational corporations are uniting, so should antitrust agencies that regulate them. Antitrust agencies around the world are realizing that the consumers whom they are mandated to protect are being adversely affected by decisions made beyond their national borders. By using the "effects" test, countries bring within their jurisdiction review of any merger or acquisition involving foreign companies with significant revenue or assets within their jurisdiction. The proliferation of merger control laws, in the absence of a mechanism to coordinate the transnational merger review, places an unnecessary burden on merging parties, and runs the risk of divergent outcomes, which at times cause friction among nation-states. Both to alleviate unnecessary burdens imposed on corporations and to reduce inefficiencies produced by the disparate review of a single transnational merger by several countries, this thesis proposes an International Merger Control Regime integrated into the WTO. The proposal focuses on ways to operationalize a "Lead Jurisdiction" model of oversight rather than on the creation of a new supranational decision-making agency. WTO dispute settlement and arbitration would be used to resolve conflicts arising out of the inability of a Lead Jurisdiction to arrive at an outcome satisfactory to other significantly affected jurisdictions.
Identifier: https://escholarship.mcgill.ca/concern/theses/2z10wr888
Keywords: International merger control; Merger; Merger control